The influence of firm financial position and industry characteristics on capital structure adjustment. (7th May 2014) - Smith, David J.; Chen, Jianguo; Anderson, Hamish D.
Abstract: We extend Byoun's (2008) modelling of the relationship between deficits and surpluses and adjustment speed, to demonstrate how industry characteristics identified by Kayo and Kimura (2011), including industry concentration, industry munificence and industry dynamism, impact on speed of adjustment. Using New Zealand firms as a case study, we find significant evidence that, as well as firm financial position, industry characteristics also impact on adjustment speed. The firm financial position results are the most robust, and we recommend further research to confirm the nature of the relationship between industry characteristics and the speed at which firms adjust towards target capital structures.